Ethnic minorities and trade: The Soviet Union as a natural experiment. (23rd April 2018) - Gokmen, Gunes; Nikishina, Elena; Vézina, Pierre‐Louis
Abstract: This paper examines the role of ethnic minorities in bilateral trade between countries of the ex‐Soviet Union. We argue that both forced re‐settlement of entire ethnic groups during the Stalin era and artificially drawn borders in Central Asia led to an exogenous ethnic composition within countries. Using data collected by ethnologists on the share of ethnic groups across countries, we build an index of bilateral ethnic networks and estimate its effect on trade using a gravity model. While ethnic networks do not seem to have played a role in inter‐republic trade during the Soviet Union, we find a positive and significant effect of ethnic networks on trade in the years following the collapse of the Soviet Union. This effect, however, eroded steadily from the early 2000s.